2015
DOI: 10.1016/j.celrep.2015.02.053
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 Is a Sensor for DNA Interstrand Crosslinks and Recruits FANCD2 to Initiate the Fanconi Anemia Pathway

Abstract: SummaryThe Fanconi anemia (FA) pathway is critical for the cellular response to toxic DNA interstrand crosslinks (ICLs). Using a biochemical purification strategy, we identified UHRF1 as a protein that specifically interacts with ICLs in vitro and in vivo. Reduction of cellular levels of UHRF1 by RNAi attenuates the FA pathway and sensitizes cells to mitomycin C. Knockdown cells display a drastic reduction in FANCD2 foci formation. Using live-cell imaging, we observe that UHRF1 is rapidly recruited to chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 27 publications
1
89
0
Order By: Relevance
“…However, additional components of this pathway in higher eukaryotic systems remain unknown. For example, there is no clear mammalian Saw1 homolog, although a recent study has proposed that the ICL repair sensor UHRF1 is a functional homolog [89]. It will be interesting to test whether UHRF1 and SLX4 are required for mammalian SSA.…”
Section: Annealing-dependent Dsb Repairmentioning
confidence: 99%
“…However, additional components of this pathway in higher eukaryotic systems remain unknown. For example, there is no clear mammalian Saw1 homolog, although a recent study has proposed that the ICL repair sensor UHRF1 is a functional homolog [89]. It will be interesting to test whether UHRF1 and SLX4 are required for mammalian SSA.…”
Section: Annealing-dependent Dsb Repairmentioning
confidence: 99%
“…One of the most interesting is a sensor role for interstrand crosslinks, showing that UHRF1 is also involved in DNA repair processes [2022]. Of note, it was also shown that the decrease of UHRF1 protein levels is a major cause of DNA demethylation in embryonic stems cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…66 SRA domain recognizes and recruits UHRF1 to the interstrand crosslinks (ICLs) of DNA caused by various genotoxic agents such as mitomycin C and psoralen derivative 4,5′,8-trimethylpsoralen (TMP). 67 In vivo cell imaging demonstrated direct involvement of UHRF1 in triggering recruitment of Fanconi anemia group D2 (FANCD2) to ICL for initiation of DNA repair. 67 UHRF1 also acted as a scaffold for recruitment of endonucleases which are required for repairing ICL lesions.…”
Section: Involvement Of Uhrf1 In Dna Repairmentioning
confidence: 99%
“…67 In vivo cell imaging demonstrated direct involvement of UHRF1 in triggering recruitment of Fanconi anemia group D2 (FANCD2) to ICL for initiation of DNA repair. 67 UHRF1 also acted as a scaffold for recruitment of endonucleases which are required for repairing ICL lesions. In HeLa nuclear extract, UHRF1 interacted and regulated the activity of Mus81-EME1 and ERCC1-XPF endonucleases which initiate incision and unhooking of ICLs.…”
Section: Involvement Of Uhrf1 In Dna Repairmentioning
confidence: 99%